The Question of Grammatical Equivalence in Translation - Sudartini, Siti (Journal of English and Education (JEE), 2009)
This study is concerned with three aspects of grammatical equivalence occurring in translation, namely, person, tense and voice. In particular, this study tries to answer some questions related to the notion of grammatical equivalence in English-Bahasa Indonesia translation related to the categories of person (pronoun), tenses, and voice. This study is a descriptive qualitative one which tries to describe and delineate the phenomenon of translation naturally without the intervention of an experiment or an artificially contrived treatment. This kind of study requires a holistic perspective of there search area in order to gather as much information as possible and to avoid any manipulation or interference in the study context. The results of the study have shown the followings. Firstly, most of the English pronouns with person reference are translated by the personal pronouns in Bahasa Indonesia, some are not translated by the personal pronouns in Bahasa Indonesia since their meaning are considered known from their context, and some other are not translated by personal pronouns but rather by repeating then our reference. Secondly, the category of tense in Englis his presented morphologically by changing the verb forms whereas in Bahasa Indonesia it is presented lexically by adding words indicating the time relation of the event presented by the verb. Thirdly, both English and Bahasa Indonesia have the category of voice but they do not always use this category with the same frequency. The active forms in English are not always translated into active forms in Bahasa Indonesia, and vice versa.